Integrating play-based pedagogy into a knowledge-based curriculum: supporting children’s understanding of anger in a Chinese kindergarten - Liu, Qiming; Demetriou, Helen (Frontiers in Psychology, 2025)
IntroductionWe examined whether culturally adapted play can support anger understanding within knowledge‑based Chinese kindergarten curricula.MethodsOne‑week plan with 40 children (5–6 years) and four teachers; mixed play types across five MoE domains. Outcomes: oral assessment by domain and teacher interviews; descriptive/thematic analyses.ResultsStrengths in language, social, arts and health; between‑class variability. Teachers noted richer emotion vocabulary, listening and peer problem‑solving; some misconceptions persisted.DiscussionTeacher‑centred, culturally appropriate play can be embedded but needs teacher development; longer, controlled evaluations are recommended.